Visceral adiposity index is highly associated with adiponectin values and glycaemic disturbances. (20th December 2012) - Al‐Daghri, Nasser M.; Al‐Attas, Omar S.; Alokail, Majed S.; Alkharfy, Khalid M.; Charalampidis, Paris; Livadas, Sarantis; Kollias, Anastasios; Sabico, Shaun Louie; Chrousos, George P.
Abstract Background Visceral Adiposity Index (VAI) is a gender‐specific mathematical index estimated with the use of simple anthropometric (body mass index and waist circumference) and biochemical (triglycerides and high density lipoprotein cholesterol) parameters. Recent studies have shown that VAI reflects accurately the degree of visceral adiposity and insulin resistance. However, up to now, VAI has not been evaluated if it correlates with carbohydrate metabolism disorders, as well as with adipokine secretion from the fat mass. Methods In a cohort of 308 out of 414 adult Saudi subjects screened for the study, detailed personal medical history, anthropometrics and metabolic/hormonal profiles were obtained. Additionally, the circulating concentrations of several circulating adipokines, namely adiponectin, leptin, tumour necrosis factor‐α (TNF‐α) and resistin, were measured. Results Stepwise multivariate analysis showed that VAI was the sole determinant of adiponectin levels (R2 = 0·07, beta ± SE: −0·25 ± 0·05), while BMI and female gender predicted leptin levels (R2 = 0·26, 0·10 ± 0·01 and 0·61 ± 0·15, respectively). Furthermore, the presence of impaired fasting glucose (IFG)/diabetes was predicted only by age and VAI. Conclusions We report for the first time the direct relations of VAI with adipose tissue secretion, as well as with functional glycaemic disorders. Because VAI is estimated easily with data obtained in everyday practice, it could be used as an indirect index of adiponectin levels and the risk of impaired glucose metabolism.